A Ressignificação da vida através da morte entre os Boe Bororo: etnoterapia no luto durante os rituais fúnebres - Santos , Thais Aparecida Batista dos (2025)
The aim of the study is to explore, anchored in Indigenous Anthropology, the different views that the Boe Bororopeople (as they call themselves) have of death, the magical and biological phenomena that surround it, and the waythey deal with mourning, based on the therapeutic ethics of ancestral knowledge and the cultural ordering of society,guided by the preservation of their myths. Although there is a vast ethnographic production about these peoples, thereis a gap in the discussion about how they re-signify the cycle of social life, even in the face of mourning and theinevitability of death and dying. Maintaining systematically organized mortuary rituals, the Boe Bororo are knownfor practicing the longest funeral ceremonies among Brazil’s indigenous communities. Thus, by following aheterogeneous and multifactorial dynamic in the execution of their traditional rituals, the analysis focuses on thestrategies they develop to cope with death and the search for spiritual healing of the bereaved, in the face of the newspace they come to occupy in the community. These alternatives are often supported by traditional medicine, resultingfrom the use of plants, body paintings and specific rites for caring for the body of the dead and the mourners (they arealways guided by the exegesis of their cosmogony). These elements are the analytical focus of this investigation. Thisstudy has a qualitative methodological approach, developed through a bibliographic review (ethnographic andhistorical texts, scientific articles, dissertations and theses) and using audiovisual and ethnographic productionsrelating to history, traditional ceremonies (specifically mortuary rituals) and traditional Bororo medicine practices asthe means of theoretical foundation. Concepts such as Death, Mourning, Resignification and Ethnotherapy arefundamental to understanding the nature of the analysis that underpins the entire work. Despite the extensive anthropological and ethnographic literature produced on the Bororo and their rich mortuaryrituals, it can be seen that there is a gap in the discussions about how the Bororo, when faced with the “great illness”of death, elaborate the loss and resignify mourning by activating “mourning appeasement” devices based on themaintenance of their ancestral medical knowledge and ethno-knowledge for the spiritual and emotional care of thebereaved and the body of the deceased. It suggests that, for the Boe Bororo, the event of death is not just seen as the biological end of being, but is the centerof social transformations, strengthening the role of the individual in society and ensuring the continuity of life. Beingcelebrated even more than birth, the cult of the dead reinforces the cultural identity of this group, while themaintenance of ceremonial life (which recalls their myths) and the operationalization of ancestral ethno-knowledgeare the insignia that give new meaning to their (re)existence in the face of the growing violation of their sacred space: nature. Furthermore, the results obtained show that the extremely rich and complex funeral ceremonies of thesepeoples make us reflect on the possibilities of a theoretical, anthropological and methodological expansion withinThanatology, when we consider the perceptions and ritualizations of death in various societies. This is due to the factthat the response to this natural and social phenomenon is, firstly, polysemic in different human groups.